Ensuring food security under martial law - Bilousova, Liudmyla; Pchelenko, Anastasiia; Omelchenko, Mariia; Kuzmin, Oleg (My University, 2023)
У статті розглянуто проблеми продовольчої безпечності в Україні в умовах воєнного стану. Окремо висвітлено токсичні ризики забруднення довкілля внаслідок війни, що значно впливає на екологію та здоров’я населення України.

The article examines the problems of food security in Ukraine under martial law. In addition, toxic risks of environmental pollution as a result of the war, which affects the ecology and health of the population of Ukraine, were revealed
Keywords: кафедра технології ресторанної і аюрведичної продукції; продовольча безпечність; food security; HACCP; martial law; воєнний стан